Changes in Financial Habits Caused by Fintech in Peru - Mejía Díaz, Cristian Alexander (2023)
The goal of this study is to identify changes in the financial habits of the Peruvian population as a result of the growth and use of financial technologies. The study was conducted in a context where habits can be influenced by these technologies, consequently leading users to employ digital methods that can offer benefits such as time saving, satisfaction and security. Mobile payment and currency exchange financial verticals were defined for the scope of this project. A survey was conducted on a sample of 384 users obtained from the database of a prominent bank in the country. It aims to obtain the users’ perception of the benefits and illustrate their new habits regarding financial operations. The use of fintech has had a clear impact on the way financial operations are done, generating new, more digital habits.